Storying special objects: Material culture, narrative identity and life story work for children in care. (July 2020) - Watson, Debbie; Hahn, Rachel; Staines, Jo
This paper considers the importance of material objects for looked after and adopted children integrated as part of life story work practices. Conducting life story work is believed to be good practice within direct work with looked after children in England and there are a range of diverse practices, including life story books, later life letters and memory boxes. Through a creative design project developing a playful memory product for looked after children, we have had the opportunity to capture sector perspectives on life story work approaches and these are interspersed throughout this commentary. Combining multi-disciplinary theoretical perspectives and these sector insights, we explore how special material objects are important for children's identity and continuity of sense of self. The paper highlights the importance of children telling their own stories of these objects, giving them agency and control over their life story narratives. In a context of austerity, life story work may not be prioritised by social workers who have many other competing demands and limited resources. We emphasise the need for professionals to recognise the value children give to objects and to provide them with opportunities to both keep these safe during placement moves and to tell their own story through their objects alongside more traditional, formal life story work. The recommendations have implications for children in out of home care in many country contexts, not just England where the research has been conducted.